Load-deflection and surface properties of coated and conventional superelastic orthodontic archwires in conventional and metal-insert ceramic brackets - Shiva Alavi; Navid Hosseini (Wolters Kluwer Medknow Publications, 2012)
Background: Properties of coated archwires, which have been introduced for esthetic demands during orthodontic treatments, along with the use of tooth-colored brackets, are not clear. The aim of this study is to compare the load-deflection and surface properties of coated superelastic archwires with conventional superelastic archwires in conventional and metal-insert ceramic brackets. Materials and Methods: In this experimental study, 3 types of archwires including ultraesthetic polycoated, ultraesthetic epoxyresin coated and conventional (uncoated) superelastic nickel-titanium (NiTi) archwires were used in each of 2 types of brackets including conventional and metal-insert ceramic. To simulate oral environment, all specimens were incubated in artificial saliva using thermocycling model and then were tested in three-bracket bending test machine. Loading and unloading forces, plateau gap and end load deflection point (ELDP) were recorded. Archwires were investigated with a stereomicroscope before and after the experiment. Two-way ANOVA and Tukey tests were used at P<0.05. Results: Epoxyresin archwires produced lower forces (19 to 310 gr) compared to polycoated (61 to 359 gr) and NiTi (61 to 415 gr) (P<0.0001). The maximum ELDP (0.43 mm) was observed in epoxyresin archwires (P<0.001). Coatings of some epoxyresin wires were torn and of polycoated wires peeled off. Conventional ceramic bracket produced higher loading forces with polycoated and NiTi archwires and lower unloading forces with all 3 types of archwires compared to metal-insert type (P<0.05). Conclusion: Epoxyresin-coated archwire had the lowest force and highest ELDP. Coatings were not durable in these experimental conditions. Conventional ceramic bracket produced higher frictional force compared to metal-insert type.